Proceedings of the 19th ACM International Conference on Multimodal Interaction 2017
DOI: 10.1145/3136755.3136759
|View full text |Cite
|
Sign up to set email alerts
|

GazeTap: towards hands-free interaction in the operating room

Abstract: During minimally-invasive interventions, physicians need to interact with medical image data, which cannot be done while the hands are occupied. To address this challenge, we propose two interaction techniques which use gaze and foot as input modalities for hands-free interaction. To investigate the feasibility of these techniques, we created a setup consisting of a mobile eye-tracking device, a tactile floor, two laptops, and the large screen of an angiography suite. We conducted a user study to evaluate how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 44 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…A reoccurring problem with existing POC systems is that health care workers cannot use them when they do not have their hands free. This is especially problematic in health care where many procedures need to be performed aseptically (Hatscher et al 2017). In this regard, smartphones, tablets and laptops are not well suited for documentation at the POC, because they should not be touched while the practitioner's hands are sterile or soiled.…”
Section: Wound Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…A reoccurring problem with existing POC systems is that health care workers cannot use them when they do not have their hands free. This is especially problematic in health care where many procedures need to be performed aseptically (Hatscher et al 2017). In this regard, smartphones, tablets and laptops are not well suited for documentation at the POC, because they should not be touched while the practitioner's hands are sterile or soiled.…”
Section: Wound Managementmentioning
confidence: 99%
“…The digital transformation is recognized as a key component to tackle this challenge (Gopal et al 2019). Due to hygienic requirements hands-free technology interaction is often required in the health care sector (Hatscher et al 2017). Established smart devices like smartphones and tablets are not an optimal fit.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…More complex gestures, such as drag and drop and similar interactions involving multiple objects, are possible, but the impact on the usability still needs to be evaluated. Hatscher et al confirmed gaze interactions as an excellent modality for pointing tasks but found that it can easily interfere when other body parts are used for interaction …”
Section: Discussionmentioning
confidence: 99%
“…Hatscher et al confirmed gaze interactions as an excellent modality for pointing tasks but found that it can easily interfere when other body parts are used for interaction. 30 We measured the workload of the participants using NASA Raw-TLX. The subscales show that, although users were confronted with a new interaction technique, frustration and physical demand were low.…”
Section: Discussionmentioning
confidence: 99%
“…Gaze gestures ofer a natural appeal for applications in Human-Computer Interaction. Smooth pursuit eye movements have demonstrated encouraging interaction modalities, they unveil a higher degree of privacy preservation, i.e., they allow users to interact with computing machines conidently [21,36]. As such, their investigations in passwords and PINs entry mechanism for user identiication are gaining considerable attention [8].…”
Section: Introductionmentioning
confidence: 99%